Cyberbullying – A Critical Analysis of Laws, Criminal Responsibility and Jurisdiction - KHUDHAIR, NIBRAS SALIM (The journal of contemporary issues in business and government, 2021)
It is vital to look upon the data of Cyber Bullying cases and the age for which the accused is held responsible. Statistics reveals that criminal minded people who are on the borderline of the ‘age’ who could be charged under IPC for some blunt crimes are being treated liberally. Cyberbullying, also known as Internet bullying, is a form of criminal activity that falls under the broadcategory of cybercrime. Since there are different types of cyberbullying and abuse, it’s crucial to know what counts as “cyberbullying.” If we look at the dictionary meaning of a bully, we can see that it is described as “seek to hurt, threaten, or coerce - someone perceived as vulnerable”. Bullying is described as any individual or group of individuals who seeks to injure, coerce, intimidate, or threaten another.Such actions or action are most commonly seen on social media sites as well as in chat boxes and gaming websites. Cyberbullying occurs when an individual or group of people bullies or harasses another person using digital technology on the internet or in another digital sphere. This can include things like posting private photographs and videos without permission, creating fake accounts and spamming groups or individuals online, body shaming, making memes and videos of people, often celebrities, making mess ups or slips, and so on. According to a 2016 UNICEF survey, one in every three internet users worldwide is a child, while the latest ‘India Internet Report 2019’ indicates that two out of every 3internet users in India are between the ages of 12 and 29. As a result of their psychological nature, this community of internet users is often targeted by online bullies. The number of incidents of cyberbullying and abuse has increased as a result. Indian women and teenagers became the victim of Cyberbullying and cases increased by 36% in just one year.